Faktor Yang Mempengaruhi Pemahaman Santri Terhadap Kitab I’anatut Thalibin Di Dayah Takwinul Mumtazi Kabupaten Aceh Utara - Mannan Mannan (Journal of Islamic Education and Law, 2026)
This study aims to identify the factors influencing students’ understanding of the I’anatut Thalibin classical Islamic text at Dayah Takwinul Mumtazi. The study employed a qualitative approach with a descriptive research design. The research subjects consisted of the educational director, teachers (ustadz), and students (santri). Data were collected through observation, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The findings revealed that the students' understanding of the I’anatut Thalibin text was generally good. This was evident from their ability to recall and explain concepts learned in previous lessons, classify discussions according to the learning materials, and explain topics based on chapters they had studied, such as wudhu (ablution) and prayer. The students were also able to provide examples related to the materials learned. Furthermore, some students demonstrated the ability to present the content according to the learning concepts by correctly reading and interpreting the text, enabling them to develop broader interpretations of the subject matter. They were able to explain the meanings of the lessons in simple language, making the content easier to understand and apply in their daily lives. The factors influencing students’ understanding of the I’anatut Thalibin text at Dayah Takwinul Mumtazi were categorized into two groups: internal and external factors. Internal factors originated from the students themselves and included Arabic language proficiency, interest in reading classical Islamic texts, educational background, and motivation. External factors stemmed from the students’ environment and included teaching methods, classroom environment, learning resources, and learning evaluation.